Euro 2012 in Poland – facts and myths about its importance for the development of the host regions in the context of the counterfactual analysis - Joanna Kudełko; Zbigniew Mogiła; Aleksandra Poproch (European Regional Science Association (ERSA), 2012)
In April 2007 UEFA's Executive Committee announced that the 2012 European Football Championship, commonly referred to as Euro 2012, will be hosted by Poland and Ukraine between 8 June and 1 July 2012. The UEFA's decision gave rise to expectations that the organization of such a prestigious international sports event would be a great opportunity to improve the tourist and investment attractiveness of the host regions. It was primarily expected that Euro 2012 tournament will speed up building and modernization of communication, sports and touristic infrastructures which –in turn- will spur economic development of the Polish host regions. The main aim of this paper is to present the quantitative impact of public investments and tourist expenditures associated with Euro 2012 on the development of the four Polish host regions- Dolnośląskie, Mazowieckie, Pomorskie and Wielkopolskie. The analysis is carried out on the basis of the two main baseline scenarios: 1) Non-Euro 2012 scenario assuming that all the investment associated with the tournament would have been undertaken in any case with a 4 year delay due to the fact that most of them is financed form the EU funds which must be implemented until 2015; 2) Euro 2012 scenario assuming that the tournament has accelerated public investments up to 4 years in comparison to the non-Championship scenario. Moreover, within the Euro 2012-scenario two sub-scenarios regarding the potential number of tourists are constructed. The analysis is conducted using the regional HERMIN models and concentrates on such macroeconomic indicators as GDP per capita, employment and investment. The research period is 2008 (beginning of investment)-2020 in order to derive both short-term (demand) and long-term (supply) effects. The results are compared and confronted with the analogues effects for other European regions in order to formulate general conclusions on the role of such events in the regional development.
Keywords: R11; 330; Euro 2012 in Poland; development of the regions; counter-factual macroeconomic simulations